Dimeric procyanidins are inhibitors of NF-κB–DNA binding - Mackenzie, Gerardo G. (2009)
Given the central role of the transcription factor NF-kB in inflammation, molecules that can inhibit NFkB are being actively investigated. The present work characterize potential interactions between dimeric procyanidins [B-type (B1 and B2) and A-type (A1 and A2)] and NF-kB proteins. B1 and B2, inhibited tumor necrosis factor a (TNFa)- and phorbol 12-myristate 13-acetate (PMA)-induced transactivation of NF-kB-driven genes and the increase of NF-kB–DNA nuclear binding in Jurkat T cells. B1 and B2, added in vitro to nuclear fractions, inhibited NF-kB binding to its DNA consensus sequence. B1 and B2 prevented the binding of RelA and p50 recombinant proteins to its DNA consensus sequence. All these effects were not observed with A1 and A2. Putative molecular models for possible interactions of B1, B2, A1 and A2, with NF-kB proteins were constructed, indicating that B-type dimeric procyanidins have higher possibilities of chemical interactions with NF-kB than A-type dimeric procyanidins. The results support the concept that B-type dimeric procyanidins can provide anti-inflammatory benefits due to their ability to reduce NF-kB binding to the DNA.